Anode for lithium secondary battery, method for producing anode for lithium secondary battery, and lithium secondary battery including anode
A double-layered negative electrode structure with a carbon-based layer to manage volume expansion and a silicon-based layer for rapid charging addresses the performance issues of silicon-based electrodes, ensuring high capacity and extended cycle life in lithium secondary batteries.
Patent Information
- Application Number
- JP2024542059
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-07-11
- Filing Date
- 2023-07-12
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2043-07-12
AI Technical Summary
Lithium secondary batteries face challenges with silicon-based negative electrodes, which exhibit rapid volume expansion during charging and discharging, leading to structural damage and reduced performance, particularly in quick charging applications.
A double-layered negative electrode structure is employed, comprising a first carbon-based layer to suppress volume expansion and a second silicon-based layer to enhance rapid charging performance, with specific thickness and composition ratios to minimize lithium precipitation and dendrite formation.
The double-layered structure effectively suppresses volume expansion and lithium precipitation, maintaining high capacity and rapid charging performance while extending the battery's cycle life.
Smart Images

Figure 2025502281000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of the filing date of Korean Patent Application No. 10-2022-0086772, filed with the Korean Intellectual Property Office on July 14, 2022, the entire contents of which are incorporated herein by reference.
[0002] The present application relates to a negative electrode for a lithium secondary battery, a method for producing a negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode. [Background technology]
[0003] The rapid increase in the use of fossil fuels has led to an increased demand for alternative and clean energy, and one of the most actively researched fields in this area is power generation and storage using electrochemical reactions.
[0004] At present, a representative example of an electrochemical element that utilizes such electrochemical energy is a secondary battery, and the range of its use is tending to expand more and more.
[0005] As technological development and demand for mobile devices increases, the demand for secondary batteries as energy sources is rapidly increasing. Among such secondary batteries, lithium secondary batteries, which have high energy density and voltage, long cycle life, and low self-discharge rate, have been commercialized and are widely used. In addition, research into a method for manufacturing a high-density electrode with a higher energy density per unit volume as an electrode for such high-capacity lithium secondary batteries is being actively conducted.
[0006] In general, a secondary battery is composed of a positive electrode, a negative electrode, an electrolyte, and a separator. The negative electrode includes a negative electrode active material that inserts and removes lithium ions from the positive electrode. Silicon-based particles having a large discharge capacity can be used as the negative electrode active material.
[0007] In particular, in recent years, in response to the demand for high-density energy batteries, active research has been conducted into methods of increasing capacity by using silicon-based compounds such as Si / C and SiOx, which have a capacity 10 times larger than that of graphite-based materials, as negative electrode active materials. However, in the case of silicon-based compounds, which are high-capacity materials, they are materials with a large capacity compared to conventionally used graphite and have excellent capacity characteristics, but their volume expands rapidly during charging, cutting off the conductive path and reducing battery characteristics, resulting in a decrease in capacity from the beginning. In addition, when silicon-based negative electrodes undergo repeated charge and discharge cycles, lithium ions are not uniformly charged in the depth direction of the negative electrode, and reactions proceed on the surface, accelerating surface deterioration, so performance needs to be improved in terms of battery cycles.
[0008] Graphite electrodes have better life characteristics than silicon-based electrodes, but are inferior in fast charging performance. In recent years, as lithium secondary batteries have been widely used, research is being conducted to shorten the charging time of lithium secondary batteries, and it is now necessary to complete charging of lithium secondary batteries within at least 20 minutes. To improve fast charging performance, silicon-based anodes, which have high capacity and potential compared to graphite, are used, but silicon-based anodes have the above-mentioned problems due to structural changes and collapse caused by their high capacity, and when silicon-based and graphite-based electrodes are mixed, the structure of the graphite electrode is also destroyed, resulting in a significant decrease in life characteristics.
[0009] In order to solve the above problems when using a silicon-based compound having excellent fast charging performance alone as a negative electrode active material, various methods have been discussed, such as a method of adjusting the driving potential, a method of further coating a thin film on the active material layer, a method of suppressing the volume expansion itself such as a method of adjusting the particle size of the silicon-based compound, or the development of a binder that suppresses the volume expansion of the silicon-based compound to prevent the conductive path from being broken.
[0010] However, in the case of the above method, there is a limit to its application since it may deteriorate the performance of the battery, and there is still a limit to the commercialization of the manufacture of negative electrode batteries having a high content of silicon-based compounds, which have excellent fast charging performance. As the ratio of silicon-based active material contained in the silicon-based active material layer increases, pre-lithiation is concentrated on the surface of the negative electrode, and damage is caused to the silicon-based active material on the surface side, and non-uniform pre-lithiation occurs, causing problems in improving life characteristics.
[0011] Therefore, in order to improve the rapid charging performance of lithium secondary batteries, research is needed into lithium secondary batteries that use silicon-based negative electrodes, which are high-capacity materials, and that can ensure long-life characteristics. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] JP 2009-080971 A Summary of the Invention [Problem to be solved by the invention]
[0013] In the present application, it has been confirmed through research that, while using a carbon-based active material in the negative electrode, a silicon-based composition, which is a high-capacity material, is coated within the range of Formula 1 below to form a silicon-based buffer layer, thereby ensuring the fast charging performance, which has been a problem in the past, and further improving both the capacity characteristics and the cycle performance. Therefore, the present application relates to a negative electrode for a lithium secondary battery, a method for manufacturing a negative electrode for a lithium secondary battery, and a lithium secondary battery including the negative electrode. [Means for solving the problem]
[0014] One embodiment of the present specification is a negative electrode for a lithium secondary battery including: a negative electrode current collector layer; a first negative electrode active material layer provided on one or both surfaces of the negative electrode current collector layer; and a second negative electrode active material layer provided on the surface of the first negative electrode active material layer opposite to the surface in contact with the negative electrode current collector layer. The first negative electrode active material layer includes a first negative electrode active material layer composition containing a first negative electrode active material, the second negative electrode active material layer includes a second negative electrode active material layer composition containing a second negative electrode active material, the second negative electrode active material layer includes one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), and SiC, the first negative electrode active material includes one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing nitride, and based on 100 parts by weight of the first negative electrode active material, the silicon-based active material is included in an amount of 5 parts by weight or less, and a negative electrode for a lithium secondary battery satisfying the following formula 1 is provided. [Formula 1] 0.1 ≦ [B / (A + B)] × 100 (%) ≦ 15
[0015] In Formula 1, A is the total thickness of the first negative electrode active material layer, which is 30 μm or more and 150 μm or less, B is the total thickness of the second negative electrode active material layer.
[0016] In another embodiment, a method for manufacturing a negative electrode for a lithium secondary battery includes: preparing a negative electrode current collector layer; applying a first negative electrode active material layer composition on one or both surfaces of the negative electrode current collector layer to form a first negative electrode active material layer; and applying a second negative electrode active material layer composition on the surface of the first negative electrode active material layer opposite to the surface in contact with the negative electrode current collector layer to form a second negative electrode active material layer. The second negative electrode active material includes one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), and SiC, the first negative electrode active material includes one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing nitride, and based on 100 parts by weight of the first negative electrode active material, the silicon-based active material is included in an amount of 5 parts by weight or less, and a method for manufacturing a negative electrode for a lithium secondary battery satisfying the formula 1 is provided.
[0017] Finally, provided is a lithium secondary battery including a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator provided between the positive electrode and the negative electrode; and an electrolyte.
Advantages of the Invention
[0018] The negative electrode for a lithium secondary battery according to an embodiment of the present invention has a double-layer active material layer composed of a first negative electrode active material layer and a second negative electrode active material layer. In particular, the second negative electrode active material contained in the second negative electrode active material layer includes at least one selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), and SiC.
[0019] At this time, by satisfying the thickness in the range of Formula 1 for the second negative electrode active material layer of the negative electrode for a lithium secondary battery according to the present application, the rapid charging performance can be maximized by thinly coating the second negative electrode active material layer having high-capacity characteristics. Lithium precipitation due to rapid charging, which is a conventional problem, will occur due to a graphite-based active material whose potential becomes negative by charging at a high C-rate, but it has a feature capable of solving such a problem.
[0020] Further, the first negative electrode active material may include one or more selected from the group consisting of a carbon-based active material, SiOx (0 < x < 2), SiC, and Si alloy, and particularly may include a carbon-based active material and SiOx (0 < x < 2).
[0021] That is, in the negative electrode for a lithium secondary battery according to the present application, since the second negative electrode active material layer is present at the uppermost end, lithium deposition due to the graphite-based active material described above is formed between the first negative electrode active material layer and the second negative electrode active material layer, thereby suppressing the formation of lithium dendrites on the surface of the negative electrode, and thus there is no short circuit problem, and since the silicon potential is high, lithium moves smoothly to the second negative electrode active material layer. In conclusion, the negative electrode for a lithium secondary battery according to the present application has a double layer structure with a specific composition, and by controlling the thickness range within the range of Formula 1, the probability of problems caused by lithium deposition is very low.
[0022] In conclusion, the negative electrode for a lithium secondary battery according to the present application has the advantage of rapid charging of an electrode using a high content of Si particles as a single-layer active material, while resolving the disadvantages of having such an electrode, such as surface deterioration, uniformity during pre-lithiation, and life characteristics, by configuring the first negative electrode active material layer and the second negative electrode active material layer as a double layer and applying a specific composition and thickness. [Brief description of the drawings]
[0023] [Figure 1] FIG. 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0024] Before describing the present invention, some terms will first be defined.
[0025] In this specification, when a part is said to "comprise" a certain component, this means that it may further include other components, rather than excluding other components, unless specifically stated to the contrary.
[0026] In this specification, "p to q" means a range of "not less than p and not more than q".
[0027] In this specification, the "specific surface area" is measured by the BET method, and specifically, is calculated from the amount of nitrogen gas adsorption at liquid nitrogen temperature (77K) using a BELSORP-mini II manufactured by BEL Japan Co., Ltd. That is, in this application, the BET specific surface area may mean the specific surface area measured by the above-mentioned measurement method.
[0028] In this specification, "Dn" means particle size distribution, and refers to the particle size at the n% point of the cumulative particle number distribution by particle size. That is, D50 is the particle size (average particle size) at the 50% point of the cumulative particle number distribution by particle size, D90 is the particle size at the 90% point of the cumulative particle number distribution by particle size, and D10 is the particle size at the 10% point of the cumulative particle number distribution by particle size. Meanwhile, the particle size distribution can be measured using the laser diffraction method. Specifically, the powder to be measured is dispersed in a dispersion medium, and then introduced into a commercially available laser diffraction particle size measuring device (e.g., Microtrac S3500), and the difference in the diffraction pattern due to the particle size when the particles pass through a laser beam is measured to calculate the particle size distribution.
[0029] In this specification, when a polymer contains a certain monomer as a monomer unit, it means that the monomer is involved in a polymerization reaction and is contained as a repeating unit in the polymer. In this specification, when a polymer contains a monomer, this is interpreted as the same as when a polymer contains a monomer as a monomer unit.
[0030] In this specification, the term "polymer" is understood to be used in a broad sense including copolymers, unless otherwise specified as a "homopolymer."
[0031] In this specification, the weight-average molecular weight (Mw) and the number-average molecular weight (Mn) are the polystyrene-equivalent molecular weights measured by gel permeation chromatography (GPC) using monodisperse polystyrene polymers (standard samples) of various degrees of polymerization commercially available for molecular weight measurement as the standard substances. In this specification, the molecular weight means the weight-average molecular weight unless otherwise specified.
[0032] Hereinafter, for those with ordinary knowledge in the technical field to which the present invention belongs to easily implement the present invention, a detailed description will be given with reference to the drawings. However, the present invention can be embodied in various different forms and is not limited to the following description.
[0033] One embodiment of this specification is a negative electrode for a lithium secondary battery including a negative electrode current collector layer; a first negative electrode active material layer provided on one or both surfaces of the negative electrode current collector layer; and a second negative electrode active material layer provided on the opposite surface of the surface of the first negative electrode active material layer in contact with the negative electrode current collector layer, wherein the first negative electrode active material layer includes a first negative electrode active material layer composition including a first negative electrode active material, the second negative electrode active material layer includes a second negative electrode active material layer composition including a second negative electrode active material, the second negative electrode active material layer includes one or more selected from the group consisting of SiOx (x = 0), SiOx (0 <x <2), and SiC, the first negative electrode active material includes one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing nitride, and based on 100 parts by weight of the first negative electrode active material, the silicon-based active material is included in an amount of 5 parts by weight or less and satisfies Formula 1, and provides a negative electrode for a lithium secondary battery.
[0034] This application is obtained by coating a silicon-based active material layer having a range of Formula 1 on the upper layer of a carbon-based negative electrode to ensure the rapid charging performance, which is a shortcoming of existing carbon-based negative electrodes. The first negative electrode active material layer (lower layer) serves to suppress the volume expansion of the second negative electrode active material layer (upper layer), and the second negative electrode active material layer (upper layer) serves to ensure the rapid charging performance.
[0035] In this case, the first negative electrode active material layer (lower layer) is mainly made of carbon-based active material, and silicon-based active material must be mixed in as in the application to ensure capacity characteristics without causing problems with life performance, and it is important to use it within a thickness range (A) that can suppress volume expansion. Also, the second negative electrode active material layer (upper layer) must be coated with a thickness that satisfies a certain range (Equation 1) with respect to the total negative electrode thickness in order to ensure both fast charging and life performance.
[0036] The negative electrode for a lithium secondary battery according to the present application has a double layer structure with a specific composition, and the thickness range is controlled within the range of formula 1, so that the probability of problems caused by lithium precipitation is very low.
[0037] 1 is a diagram showing a laminated structure of a negative electrode for a lithium secondary battery according to an embodiment of the present application. Specifically, a negative electrode for a lithium secondary battery 100 including a first negative electrode active material layer 20 and a second negative electrode active material layer 10 on one side of a negative electrode current collector layer 30 can be seen. Although FIG. 1 shows that the first negative electrode active material layer is formed on one side, it may be included on both sides of the negative electrode current collector layer.
[0038] The negative electrode for a lithium secondary battery of the present invention will be described in more detail below.
[0039] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, comprising: a negative electrode current collector layer; a first negative electrode active material layer provided on one or both sides of the negative electrode current collector layer; and a second negative electrode active material layer provided on a side of the first negative electrode active material layer opposite to a side in contact with the negative electrode current collector layer.
[0040] In one embodiment of the present application, the negative electrode current collector layer generally has a thickness of 1 μm to 100 μm. Such a negative electrode current collector layer is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery. For example, copper, stainless steel, aluminum, nickel, titanium, fired carbon, those with a surface treatment of carbon, nickel, titanium, silver, etc. on the surface of copper or stainless steel, aluminum-cadmium alloy, etc. can be used. Also, fine irregularities can be formed on the surface to strengthen the binding force of the negative electrode active material, and it can be used in various forms such as films, sheets, foils, nets, porous bodies, foams, non-woven bodies, etc.
[0041] In one embodiment of the present application, the thickness of the negative electrode current collector layer may be 1 μm or more and 100 μm or less. More preferably, it may be 1 μm or more and 80 μm or less, and even more preferably, it may be 1 μm or more and 20 μm or less.
[0042] However, the thickness can be variously deformed according to the type and use of the negative electrode used, and is not limited thereto.
[0043] In one embodiment of the present application, the second negative electrode active material may contain at least one selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), and SiC.
[0044] In one embodiment of the present application, the second negative electrode active material may be SiOx (0 < x < 2).
[0045] In one embodiment of the present application, the second negative electrode active material may be SiC.
[0046] In one embodiment of the present application, the second negative electrode active material contains at least one selected from the group consisting of SiOx (x = 0) and SiOx (0 < x < 2), and based on 100 parts by weight of the second negative electrode active material, SiOx (x = 0) is contained in an amount of 95 parts by weight or more, preferably 97 parts by weight or more, and even more preferably 99 parts by weight or more, and may be contained in an amount of 100 parts by weight or less.
[0047] In one embodiment of the present application, the second negative electrode active material may be, in particular, pure silicon (Si) particles. The use of pure silicon (Si) as the second negative electrode active material may mean that pure Si particles (SiOx (x=0)) not combined with other particles or elements are included in the above range based on 100 parts by weight of the first negative electrode active material as described above.
[0048] The second negative electrode active material used in the second negative electrode active material layer of the present invention undergoes a very complicated crystal change in the reaction of electrochemically absorbing, storing, and releasing lithium atoms. As the reaction of electrochemically absorbing, storing, and releasing lithium atoms progresses, the composition and crystal structure of the silicon particles change to Si (crystal structure: Fd3m), LiSi (crystal structure: I41 / a), Li2Si (crystal structure: C2 / m), Li7Si2 (Pbam), Li 22 Si5(F23), etc. In addition, the volume of silicon particles expands by about four times as a result of changes in the complex crystal structure. Therefore, repeated charge-discharge cycles can destroy silicon particles, and as bonds are formed between lithium atoms and silicon particles, the lithium atom insertion sites that the silicon particles initially had can be damaged, resulting in a significant decrease in cycle life.
[0049] In one embodiment of the present application, the second negative electrode active material may consist of SiOx (x=0).
[0050] The second negative electrode active material layer according to the present application contains a second negative electrode active material, specifically, pure silicon particles containing 95 parts by weight or more of SiOx (x=0). In this case, when the pure silicon particles are contained in a high content, excellent capacity characteristics can be obtained.
[0051] Meanwhile, the average particle size (D50) of the second negative electrode active material of the present invention may be 3 μm to 10 μm, specifically 4 μm to 8 μm, and more specifically 5 μm to 7 μm. When the average particle size is within the above range, the specific surface area of the particles is within an appropriate range, and the viscosity of the negative electrode slurry is formed within an appropriate range. This allows smooth dispersion of the particles constituting the negative electrode slurry. In addition, when the size of the first negative electrode active material is equal to or greater than the above lower limit range, the contact area between the silicon particles and the conductive material is excellent due to the complex of the conductive material and the binder in the negative electrode slurry, and the conductive network is more likely to be maintained, thereby increasing the capacity retention rate. Meanwhile, when the average particle size satisfies the above range, silicon particles that are too large are excluded, and the surface of the negative electrode is formed smoothly, thereby preventing the current density non-uniformity phenomenon during charging and discharging.
[0052] In one embodiment of the present application, the second negative electrode active material generally has a characteristic BET surface area. The BET surface area of the first negative electrode active material is preferably less than 0.01 m 2 / g~150.0m 2 / g, more preferably 0.1m 2 / g~100.0m 2 / g, particularly preferably 0.2m 2 / g~80.0m 2 / g, most preferably 0.2m 2 / g~18.0m 2 / g. The BET surface area is measured according to DIN 66131 (using nitrogen).
[0053] In one embodiment of the present application, the second negative electrode active material can be, for example, in crystalline or amorphous form, and is preferably not porous.The silicon particles are preferably spherical or shard particles.Alternatively, but less preferably, the silicon particles can have a fibrous structure or be in the form of a silicon-containing film or coating.
[0054] In one embodiment of the present application, the second negative electrode active material may have a non-spherical morphology, and the sphericity is, for example, 0.9 or less, for example, 0.7 to 0.9, for example, 0.8 to 0.9, for example, 0.85 to 0.9.
[0055] In this application, the circularity is determined by the following formula 1-1, where A' is the area and P is the perimeter. [Formula 1-1] 4πA' / P 2
[0056] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, in which the second negative electrode active material is 60 parts by weight or more based on 100 parts by weight of a second negative electrode active material layer composition.
[0057] In yet another embodiment, the second negative electrode active material may be 60 parts by weight or more, preferably 65 parts by weight or more, more preferably 70 parts by weight or more, and 95 parts by weight or less, preferably 90 parts by weight or less, more preferably 80 parts by weight or less, based on 100 parts by weight of the second negative electrode active material layer composition.
[0058] In the second negative electrode active material layer composition according to the present application, even if a second negative electrode active material having an extremely high capacity is used within the above range, surface deterioration can be minimized by using a second negative electrode active material layer within a thickness range described below, and the composition has excellent fast charging performance.
[0059] In the past, it was common to use only graphite-based compounds as negative electrode active materials, but in recent years, as the demand for high-capacity batteries has increased, attempts to mix silicon-based compounds to increase capacity have been increasing. However, silicon-based compounds have a limitation in that their volume expands rapidly during the charge / discharge process, damaging the conductive path formed in the negative electrode active material layer and reducing the performance of the battery.
[0060] Therefore, in one embodiment of the present application, the second negative electrode active material layer composition may further include at least one selected from the group consisting of a second negative electrode conductive material; and a second negative electrode binder.
[0061] In this case, the second negative electrode conductive material and the second negative electrode binder contained in the second negative electrode active material layer composition may be any material commonly used in the art without any limitations.
[0062] In one embodiment of the present application, the second negative electrode conductive material may be any material that can be commonly used in the art without limitation, and may specifically include at least one selected from the group consisting of dot-shaped conductive materials; planar conductive materials; and linear conductive materials.
[0063] In one embodiment of the present application, the dot-like conductive material refers to a dot-like or spherical conductive material that can be used to improve the conductivity to the negative electrode and has conductivity without inducing a chemical change. Specifically, the dot-like conductive material may be at least one selected from the group consisting of natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, conductive fiber, fluorocarbon, aluminum powder, nickel powder, zinc oxide, potassium titanate, titanium oxide, and polyphenylene derivatives, and may preferably include carbon black in that it realizes high conductivity and has excellent dispersibility.
[0064] In one embodiment of the present application, the dot-shaped conductive material has a BET specific surface area of 40 m 2 / g or more 70m 2 / g or less, preferably 45m 2 / g or more 65m 2 / g or less, more preferably 50m 2 / g or more 60m 2 / g or less.
[0065] In one embodiment of the present application, the particle diameter of the dotted conductive material may be 10 nm to 100 nm, preferably 20 nm to 90 nm, and more preferably 20 nm to 60 nm.
[0066] In one embodiment of the present application, the second negative electrode conductive material may include a sheet conductive material.
[0067] The planar conductive material can improve conductivity by increasing surface contact between silicon particles in the negative electrode, and at the same time, can suppress the disconnection of the conductive path due to volume expansion, and can be expressed as a plate-type conductive material or a bulk-type conductive material.
[0068] In one embodiment of the present application, the sheet conductive material may include at least one selected from the group consisting of platelet graphite, graphene, graphene oxide, and graphite flakes, and may be preferably platelet graphite.
[0069] In one embodiment of the present application, the average particle size (D50) of the sheet conductive material may be 2 μm to 7 μm, specifically 3 μm to 6 μm, and more specifically 4 μm to 5 μm. If the range is satisfied, the sufficient particle size makes it easy to disperse without causing an excessive increase in the viscosity of the negative electrode slurry. Therefore, when dispersing using the same device and time, the dispersion effect is excellent.
[0070] In one embodiment of the present application, the sheet conductive material provides a negative electrode composition having a D10 of 0.5 μm or more and 1.5 μm or less, a D50 of 2.5 μm or more and 3.5 μm or less, and a D90 of 7.0 μm or more and 15.0 μm or less.
[0071] In one embodiment of the present application, the sheet conductive material may be a sheet conductive material having a high BET specific surface area; or a sheet conductive material having a low specific surface area.
[0072] In one embodiment of the present application, the sheet conductive material may be a high-specific surface area sheet conductive material or a low-specific surface area sheet conductive material without any restrictions. However, the sheet conductive material in the present application may be affected to some extent by dispersion in terms of electrode performance, and it may be particularly preferable to use a low-specific surface area sheet conductive material that does not cause dispersion problems.
[0073] In one embodiment of the present application, the sheet conductive material has a BET specific surface area of 5 m 2 / g or more.
[0074] In another embodiment, the sheet conductive material has a BET specific surface area of 5 m 2 / g or more 500m 2 / g or less, preferably 5m 2 / g or more 300m 2 / g or less, more preferably 5m 2 / g or more 250m 2 / g or less.
[0075] In another embodiment, the sheet conductive material is a high specific surface area sheet conductive material having a BET specific surface area of 50 m 2 / g or more 500m 2 / g or less, preferably 80m 2 / g or more 300m 2 / g or less, more preferably 100m 2 / g or more 300m 2 / g or less.
[0076] In another embodiment, the sheet conductive material is a sheet conductive material having a low specific surface area and a BET specific surface area of 5 m 2 / g or more 40m 2 / g or less, preferably 5m 2 / g or more 30m 2 / g or less, more preferably 5m 2 / g or more 25m 2 / g or less.
[0077] Other conductive materials may include linear conductive materials such as carbon nanotubes. The carbon nanotubes may be bundled carbon nanotubes. The bundled carbon nanotubes may include a plurality of carbon nanotube units. Specifically, unless otherwise specified, the term "bundle type" refers to a secondary shape in the form of a bundle or rope in which a plurality of carbon nanotube units are arranged in a line with the longitudinal axes of the carbon nanotube units substantially aligned in the same direction or are entangled. The carbon nanotube unit has a graphite sheet having a cylindrical shape with a nano-sized diameter and an sp2 bond structure. In this case, the graphite sheet may exhibit conductive or semiconductive properties depending on the angle and structure of the winding. The bundled carbon nanotubes may be more uniformly dispersed during the manufacture of the negative electrode than entangled carbon nanotubes, and may smoothly form a conductive network in the negative electrode, thereby improving the conductivity of the negative electrode.
[0078] In particular, the linear conductive material according to one embodiment of the present application may be a single-walled carbon nanotube (SWCNT).
[0079] The single-walled carbon nanotube is a material in which carbon atoms arranged in a hexagonal shape form a tube, and depending on its unique chirality, it can exhibit non-conductive, fully conductive or semiconductive properties. The carbon atoms are linked by strong covalent bonds, and it has tensile strength about 100 times greater than that of steel, excellent flexibility and elasticity, and is chemically stable.
[0080] The average diameter of the single-walled carbon nanotubes is 0.5 nm to 15 nm. According to an embodiment of the present invention, the average diameter of the single-walled carbon nanotubes may be 1 to 10 nm, 1 nm to 5 nm, or 1 nm to 2 nm. When the average diameter of the single-walled carbon nanotubes satisfies such a range, the electrical conductivity of the negative electrode can be maintained even if the single-walled carbon nanotubes are contained in a very small content, and a preferable viscosity and solid content can be derived during the preparation of the conductive material dispersion. The single-walled carbon nanotubes in the conductive material dispersion may be present in an entangled state (aggregate) in which they are entangled with each other. Thus, the average diameter can be derived by confirming the diameter of any entangled single-walled carbon nanotube aggregate extracted from the conductive material dispersion by SEM or TEM, and then dividing the diameter of the aggregate by the number of single-walled carbon nanotubes constituting the aggregate.
[0081] The BET specific surface area of the single-walled carbon nanotubes is 500 m 2 / g~1,500m 2 / g, or 900m 2 / g~1,200m 2 / g, specifically 250m 2 / g~330m 2 / g. When the above range is satisfied, a conductive material dispersion having a preferable solid content is obtained, and the viscosity of the negative electrode slurry is prevented from excessively increasing. The BET specific surface area can be measured by a nitrogen adsorption BET method.
[0082] The aspect ratio of the single-walled carbon nanotube may be 50 to 20,000, or the length of the single-walled carbon nanotube may be 5 μm to 100 μm, or 5 μm to 50 μm. When the aspect ratio or length satisfies such a range, the specific surface area is high, so that the single-walled carbon nanotube can be strongly attracted to the active material particles in the negative electrode. As a result, the conductive network can be smoothly maintained even when the volume of the negative electrode active material expands. The aspect ratio can be determined by averaging the aspect ratios of 15 single-walled carbon nanotubes with a large aspect ratio and 15 single-walled carbon nanotubes with a small aspect ratio when observing the single-walled carbon nanotube powder through a SEM.
[0083] The single-walled carbon nanotube has a larger aspect ratio, a longer length, and a larger volume than multi-walled or double-walled carbon nanotubes, and is therefore advantageous in that an electrical network can be constructed even when only a small amount is used.
[0084] In one embodiment of the present application, the second negative electrode conductive material may be present in an amount of 1 part by weight or more and 40 parts by weight or less based on 100 parts by weight of the second negative electrode active material layer composition.
[0085] In yet another embodiment, the second negative electrode conductive material may be 1 part by weight or more and 40 parts by weight or less, preferably 3 parts by weight or more and 30 parts by weight or less, and more preferably 3 parts by weight or more and 15 parts by weight or less, based on 100 parts by weight of the second negative electrode active material layer composition.
[0086] In one embodiment of the present application, the second negative electrode conductive material includes dot-like conductive material; sheet-like conductive material; and linear conductive material, and the dot-like conductive material:sheet-like conductive material:linear conductive material may satisfy a ratio of 1:1:0.01 to 1:1:1.
[0087] In one embodiment of the present application, the dot-shaped conductive material may be in the range of 1 part by weight or more and 60 parts by weight or less, preferably 5 parts by weight or more and 50 parts by weight or less, and more preferably 10 parts by weight or more and 50 parts by weight or less, based on 100 parts by weight of the second negative electrode conductive material.
[0088] In one embodiment of the present application, the sheet conductive material may be in the range of 1 part by weight or more and 60 parts by weight or less, preferably 5 parts by weight or more and 50 parts by weight or less, and more preferably 10 parts by weight or more and 50 parts by weight or less, based on 100 parts by weight of the second negative electrode conductive material.
[0089] In one embodiment of the present application, the linear conductive material may be in the range of 0.01 parts by weight or more and 10 parts by weight or less, preferably 0.05 parts by weight or more and 8 parts by weight or less, and more preferably 0.1 parts by weight or more and 5 parts by weight or less, based on 100 parts by weight of the second negative electrode conductive material.
[0090] In one embodiment of the present application, the second negative electrode conductive material may include a linear conductive material; and a planar conductive material.
[0091] In one embodiment of the present application, the second negative electrode conductive material may include a linear conductive material and a sheet conductive material, and the ratio of the linear conductive material:sheet conductive material may satisfy 0.01:1 to 0.1:1.
[0092] In one embodiment of the present application, the second negative electrode conductive material particularly includes a linear conductive material and a planar conductive material, and by satisfying the above-mentioned composition and ratio, respectively, the life characteristics of existing lithium secondary batteries are not significantly affected, the number of points at which charging and discharging are possible increases, and the battery has the characteristic of excellent output characteristics at a high C-rate.
[0093] The present application provides a negative electrode for a lithium secondary battery, wherein the second negative electrode conductive material includes at least a linear conductive material.
[0094] In one embodiment of the present application, the second negative electrode conductive material may be made of a linear conductive material.
[0095] In this case, the linear conductive material may be 0.1 to 2 parts by weight, or 0.1 to 0.7 parts by weight, or 0.1 to 0.3 parts by weight based on 100 parts by weight of the second negative electrode active material. When the content of the linear conductive material satisfies such a range, an electrical network can be sufficiently constructed in the negative electrode active material layer, which is advantageous in terms of mixing and coating processability during electrode preparation. In addition, in the negative electrode according to an embodiment of the present invention, since the linear conductive material is included in both the first negative electrode active material layer and the second negative electrode active material layer, the conductive network between the active materials accompanying the volume expansion and contraction of the Si electrode can be maintained, which is advantageous in terms of life and allows the rapid charging performance to be maintained. Basically, the rapid charging performance is advantageous because the Si-based negative electrode can be thin-film coated compared to graphite, and the linear conductive material maintains a robust conductive network, which is useful for rapid charging, and further helps to improve the initial rapid drop in the life of the Si-based negative electrode and maintain the life.
[0096] The second negative electrode conductive material according to the present application has a completely different structure from the positive electrode conductive material applied to the positive electrode. That is, the second negative electrode conductive material according to the present application serves to capture the contact between the silicon-based active materials, which have a very large volume expansion of the electrodes due to charging and discharging, while the positive electrode conductive material serves to provide some conductivity while acting as a buffer having a shock-absorbing function when rolled, and has a completely different structure and role from the negative electrode conductive material of the present invention.
[0097] In addition, the second negative electrode conductive material according to the present application is applied to a silicon-based active material, and has a completely different structure from a conductive material applied to a graphite-based active material. That is, a conductive material used in an electrode having a graphite-based active material has particles that are simply smaller than the active material, and therefore has the properties of improving output characteristics and imparting some electrical conductivity, and has a completely different structure and role from the first negative electrode conductive material applied together with a silicon-based active material as in the present invention.
[0098] In one embodiment of the present application, the second negative electrode binder may include at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride, polyacrylonitrile, polymethylmethacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene monomer (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, polyacrylic acid, and substances in which hydrogen of these substances is substituted with Li, Na, Ca, or the like, or may include various copolymers thereof.
[0099] The second negative electrode binder according to one embodiment of the present application plays a role in holding down the active material and conductive material in order to prevent twisting and structural deformation of the negative electrode structure during volume expansion and relaxation of the second negative electrode active material. Any common binder can be applied as long as it fulfills the above role, and specifically, a water-based binder can be used, and more specifically, a PAM-based binder can be used.
[0100] In one embodiment of the present application, the amount of the second negative electrode binder is 30 parts by weight or less, preferably 25 parts by weight or less, and more preferably 20 parts by weight or less, based on 100 parts by weight of the second negative electrode active material layer composition, and may be 1 part by weight or more, or 5 parts by weight or more.
[0101] The second negative electrode binder has a higher content than the first negative electrode active material layer described below, and can strongly suppress the first negative electrode active material layer, thereby suppressing the volume expansion of the silicon-based active material contained in the first negative electrode active material layer.
[0102] In one embodiment of the present application, the first negative electrode active material includes at least one selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing nitride, and based on 100 parts by weight of the first negative electrode active material, the silicon-based active material is included in an amount of 5 parts by weight or less.
[0103] At this time, based on 100 parts by weight of the first negative electrode active material, the silicon-based active material may be 1 part by weight or more and 5 parts by weight or less.
[0104] The first negative electrode active material layer (lower layer portion) is mainly composed of a carbon-based active material. In order to ensure the capacity characteristics, it is necessary to mix and use a silicon-based active material as in the present application to such an extent that it does not cause problems in the cycle performance, and it is important to use it in a thickness range (A) that can suppress volume expansion.
[0105] In one embodiment of the present application, the first negative electrode active material may include a carbon-based active material and a mixed composition of a silicon-based active material.
[0106] In one embodiment of the present application, the silicon-based active material included in the first negative electrode active material may include at least one selected from the group consisting of SiOx (0 < x < 2), SiC, and Si alloy.
[0107] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery including SiOx (0 < x < 2) or SiC as the silicon-based active material.
[0108] In another embodiment, the silicon-based active material included in the first negative electrode active material may include SiOx (0 < x < 2).
[0109] In another embodiment, the silicon-based active material included in the first negative electrode active material may include SiC.
[0110] The negative electrode for a lithium secondary battery according to the present application is configured with a double layer, and as described above, the first negative electrode active material layer contains the first negative electrode active material. Specifically, a carbon-based active material is used as the main active material, with or without a silicon-based active material, and as a result, the electrode has an improved life characteristic as a whole. In addition, the resulting problem of rapid charging is solved by including the above-mentioned second negative electrode active material layer.
[0111] In one embodiment of the present application, the carbon-based active material may be, for example, natural graphite, artificial graphite, expanded graphite, carbon fiber, non-graphitizable carbon, carbon black, carbon nanotubes, fullerene, or activated carbon. Any material that is commonly used in carbon materials for lithium secondary batteries may be used without limitation. Specifically, the carbon-based active material may be processed into a spherical or dot-like shape before use.
[0112] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the carbon-based active material comprises graphite, the graphite comprises artificial graphite and natural graphite, and a weight ratio of the artificial graphite to the natural graphite is 5:5 to 9.5:0.5.
[0113] The artificial graphite according to an embodiment of the present invention may be in the form of primary particles, or in the form of secondary particles formed by agglomeration of a plurality of the primary particles.
[0114] The term "initial particle" as used herein means the original particle from which other types of particles are formed, and multiple primary particles can aggregate, combine or assemble to form secondary particles.
[0115] As used herein, the term "secondary particles" refers to larger, physically distinct particles formed by the aggregation, bonding, or assembly of individual primary particles.
[0116] The primary particle artificial graphite may be produced by heat treating one or more selected from the group consisting of needle cokes, mosaic cokes, and coal tar pitch.
[0117] The artificial graphite is generally produced by carbonizing raw materials such as coal tar, coal tar pitch, and heavy petroleum oil at 2,500°C or higher, and can be used as an anode active material after such graphitization and adjusting the particle size by crushing and forming secondary particles. In the case of artificial graphite, crystals are randomly distributed within the particles, and compared to natural graphite, it has a lower degree of sphericity and a slightly pointed shape.
[0118] The artificial graphite used in an embodiment of the present invention may be MCMB (mesophase carbon microbeads), MPCF (mesophase pitch-based carbon fiber), which are widely used commercially, artificial graphite graphitized in a block form, artificial graphite graphitized in a powder form, etc. The sphericity of the artificial graphite may be 0.91 or less, or 0.6 to 0.91, or 0.7 to 0.9.
[0119] The artificial graphite may have a particle size of 5 to 30 μm, preferably 10 to 25 μm.
[0120] Specifically, the D50 of the artificial graphite primary particles may be 6 μm to 15 μm, or 6 μm to 10 μm, or 6 μm to 9 μm. When the D50 of the primary particles satisfies this range, the primary particles may be formed to a degree that they have high graphitization, and the orientation index of the negative electrode active material particles may be appropriately ensured, thereby improving the fast charging performance.
[0121] The artificial graphite secondary particles may be formed by assembling primary particles. That is, the secondary particles may be structures formed by agglomerating the primary particles to each other through an assembling process. The secondary particles may include a carbonaceous matrix that aggregates the primary particles. The carbonaceous matrix may include at least one of soft carbon and graphite. The soft carbon may be formed by heat treating pitch.
[0122] The carbonaceous matrix may be contained in the secondary particles in an amount of 8% by weight to 16% by weight, specifically 9% by weight to 12% by weight. This range is a lower level than the carbonaceous matrix content used in ordinary secondary particles of artificial graphite. This is because the particle size of the primary particles in the secondary particles is controlled, and structurally stable secondary particles can be produced even if the content of the carbonaceous matrix required for assembly is small, and the amount of primary particles constituting the secondary particles can be uniform.
[0123] The artificial graphite secondary particles may include a carbon coating layer on a surface thereof, and the carbon coating layer may include at least one of amorphous carbon and crystalline carbon.
[0124] The crystalline carbon can further improve the electrical conductivity of the negative electrode active material. The crystalline carbon may include at least one selected from the group consisting of fullerene and graphene.
[0125] The amorphous carbon can appropriately maintain the strength of the coating layer and suppress the expansion of the natural graphite. The amorphous carbon may be a carbon-based material formed by using at least one carbide selected from the group consisting of tar, pitch, and other organic substances, or a hydrocarbon as a source in a chemical vapor deposition process.
[0126] The carbonized organic matter may be a carbonized organic matter selected from carbonized sucrose, glucose, galactose, fructose, lactose, mannose, ribose, aldohexose or kedohexose, and combinations thereof.
[0127] The D50 of the secondary particles of artificial graphite may be 10 μm to 25 μm, specifically 12 μm to 22 μm, and more specifically 13 μm to 20 μm. When the above range is satisfied, the secondary particles of artificial graphite may be uniformly dispersed in the slurry, and the charging performance of the battery may be improved.
[0128] The tap density of the artificial graphite secondary particles may be 0.85 g / cc to 1.30 g / cc, specifically 0.90 g / cc to 1.10 g / cc, and more specifically 0.90 g / cc to 1.07 g / cc. When the tap density satisfies the above range, the packing of the artificial graphite secondary particles in the negative electrode can be smoothly performed, which means that the adhesive strength of the negative electrode can be improved.
[0129] The natural graphite may generally consist of plate-like agglomerates before being processed, and the plate-like particles may be produced in the form of spheres having smooth surfaces by post-processing such as particle crushing and reassembly to be used as an active material for electrode manufacture.
[0130] The natural graphite used in one embodiment of the present invention may have a sphericity of more than 0.91 and less than or equal to 0.97, or from 0.93 to 0.97, or from 0.94 to 0.96.
[0131] The natural graphite may have a particle size of 5 μm to 30 μm, or 10 μm to 25 μm.
[0132] According to an embodiment of the present invention, the weight ratio of the artificial graphite to the natural graphite may be 5:5 to 9.5:0.5, or 5:5 to 9.3:0.7, or 5:5 to 9:1, or 6:4 to 9:1. When the weight ratio of the artificial graphite to the natural graphite satisfies such a range, a better output may be exhibited, which may be advantageous in terms of life span and quick charging performance.
[0133] In one embodiment of the present application, the planar conductive material used as the negative electrode conductive material has a structure and role different from that of a carbon-based active material generally used as a negative electrode active material. Specifically, the carbon-based active material used as a negative electrode active material may be artificial graphite or natural graphite, and refers to a material that is processed into a spherical or dot-like shape to facilitate the storage and release of lithium ions.
[0134] Meanwhile, the planar conductive material used as the negative electrode conductive material is a material having a planar or plate-like shape and can be expressed as plate-like graphite. That is, it is a material contained in the negative electrode active material layer to maintain a conductive path, and does not play a role in storing and releasing lithium, but means a material for securing a planar conductive path inside the negative electrode active material layer.
[0135] That is, in the present application, the use of plate-shaped graphite as a conductive material means that it is used as a material that ensures a conductive path, rather than being processed into a planar or plate-shaped form to store or release lithium. In this case, the negative electrode active material contained therein has high capacity characteristics for storing and releasing lithium, and plays a role in storing and releasing all the lithium ions transferred from the positive electrode.
[0136] Meanwhile, in the present application, the use of a carbon-based active material as an active material means that the carbon-based active material is processed into a dot-like or spherical shape and is used as a material that serves to store or release lithium.
[0137] That is, in one embodiment of the present application, the carbon-based active material, artificial graphite or natural graphite, has a BET specific surface area of 0.1 m2 / g or more 4.5m 2 / g or less. The plate-shaped graphite, which is a planar conductive material, may be planar and have a BET specific surface area of 5 m 2 / g or more.
[0138] Representative examples of the metal-based active material include compounds containing one or more metal elements selected from the group consisting of Al, Sn, Ag, Bi, Mg, Zn, In, Ge, Pb, Pd, Pt, Ti, Sb, Ga, Mn, Fe, Co, Ni, Cu, Sr, and Ba. These metal compounds can be used in any form, such as a simple substance, an alloy, an oxide (TiO2, SnO2, etc.), a nitride, a sulfide, a boride, or an alloy with lithium, but the simple substance, an alloy, an oxide, or an alloy with lithium may have a high capacity.
[0139] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, in which the first negative electrode active material is 60 parts by weight or more based on 100 parts by weight of a first negative electrode active material layer composition.
[0140] In yet another embodiment, the first negative electrode active material may be 60 parts by weight or more, preferably 70 parts by weight or more, and 99 parts by weight or less, preferably 98 parts by weight or less, and more preferably 97 parts by weight or less, based on 100 parts by weight of the first negative electrode active material layer composition.
[0141] The first negative electrode active material layer composition according to the present application has lower capacity characteristics than the second negative electrode active material, but by using the first negative electrode active material in the above range, which has less particle cracking during charge / discharge cycles or pre-lithiation, the first negative electrode active material has the characteristic of improving the life characteristics without reducing the capacity performance of the negative electrode.
[0142] In one embodiment of the present application, the first negative electrode active material layer composition may further include at least one selected from the group consisting of a first negative electrode conductive material and a first negative electrode binder, and the second negative electrode active material layer composition may further include at least one selected from the group consisting of a second negative electrode conductive material and a second negative electrode binder.
[0143] In one embodiment of the present application, a negative electrode for a lithium secondary battery is provided, wherein the first negative electrode active material layer comprises a second negative electrode active material layer composition including: a first negative electrode active material; a first negative electrode conductive material; and a first negative electrode binder.
[0144] In this case, the above description of the second negative electrode conductive material can be applied to the first negative electrode conductive material.
[0145] In one embodiment of the present application, the first negative electrode conductive material may be present in an amount of 0.1 parts by weight or more and 20 parts by weight or less based on 100 parts by weight of the first negative electrode active material layer composition.
[0146] In yet another embodiment, the first negative electrode conductive material may be 0.1 parts by weight or more and 20 parts by weight or less, preferably 0.5 parts by weight or more and 15 parts by weight or less, and more preferably 1 part by weight or more and 10 parts by weight or less, based on 100 parts by weight of the first negative electrode active material layer composition.
[0147] In addition, the contents regarding the first negative electrode binder may be the same as those regarding the second negative electrode binder.
[0148] In one embodiment of the present application, the first negative electrode binder is 15 parts by weight or less, preferably 10 parts by weight or less, more preferably 5 parts by weight or less, and may be 1 part by weight or more, or 1.5 parts by weight or more, based on 100 parts by weight of the first negative electrode active material layer composition.
[0149] The first negative electrode active material layer according to the present application uses a carbon-based active material as a main active material, and uses less silicon-based active material, so that the binder content can be relatively less than that of the second negative electrode active material layer, thereby maximizing the content of the first negative electrode active material and maximizing the capacity characteristics. In addition, the second negative electrode active material layer contains a relatively large amount of binder, which strongly suppresses the first negative electrode active material layer, and even if the first negative electrode active material layer contains a silicon-based active material, volume expansion can be efficiently suppressed.
[0150] In one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery, wherein the first negative electrode active material layer has a total thickness of 30 μm or more and 150 μm or less, and the second negative electrode active material layer has a total thickness of 1 μm or more and 20 μm or less.
[0151] In another embodiment, the total thickness of the first negative electrode active material layer may be 30 μm or more and 150 μm or less, preferably 50 μm or more and 130 μm or less, and more preferably 90 μm or more and 120 μm or less.
[0152] In still another embodiment, the second negative electrode active material layer may have a total thickness of 1 μm or more and 20 μm or less, preferably 2 μm or more and 15 μm or less, and more preferably 4 μm or more and 15 μm or less.
[0153] In one embodiment of the present application, the total loading amount of the first negative electrode active material layer composition is 5 mg / cm 2 More than 20mg / cm 2 and the total loading amount of the second negative electrode active material layer composition is 0.1 mg / cm or less. 2 More than 5mg / cm 2 The following negative electrode for a lithium secondary battery is provided:
[0154] In yet another embodiment, the total loading amount of the first negative electrode active material layer composition is 5 mg / cm 2 More than 20mg / cm 2 Less than 6 mg / cm, preferably 2 More than 15mg / cm 2 More preferably, 7 mg / cm 2 More than 13mg / cm 2 It may be the following.
[0155] In yet another embodiment, the total loading amount of the second negative electrode active material layer composition is 0.1 mg / cm 2 More than 5mg / cm 2 Less than 0.3 mg / cm, preferably 0.3 mg / cm 2 More than 3mg / cm 2 More preferably, 0.4 mg / cm 2More than 2mg / cm 2 It may be the following.
[0156] In this case, the total thickness and the total loading amount of the first and second negative electrode active material layers are based on the case where they are formed on both sides of the negative electrode current collector layer, and when they are formed on the end surface of the negative electrode current collector layer, they may be evaluated as half the value of the above range. However, some error that is clearly not half the value may be included, specifically, the error range of ±5 μm for the thickness and ±1.5 mg / cm for the loading amount. 2 may include an error.
[0157] For example, the thickness of the first negative electrode active material layer being 30 μm means that the total thickness of the first negative electrode active material layers formed on both sides of the negative electrode current collector layer is 30 μm, and when formed on one side of the negative electrode current collector layer, it may satisfy 15 μm±5 μm.
[0158] The first negative electrode active material layer composition and the second negative electrode active material layer composition have the loading amounts, so that the ratio of the active materials contained in the first negative electrode active material layer and the second negative electrode active material layer can be adjusted. That is, the amount of the first negative electrode active material contained in the first negative electrode active material layer can be adjusted to optimize the capacity characteristics, and the amount of the second negative electrode active material contained in the second negative electrode active material layer can be adjusted to improve the life characteristics without deteriorating the capacity characteristics.
[0159] The loading amount may refer to the weight of a composition for forming a negative electrode active material layer, and specifically, the loading amount of a composition may have the same meaning as the loading amount of a slurry including the composition.
[0160] In particular, in one embodiment of the present application, there is provided a negative electrode for a lithium secondary battery which satisfies the following formula 1: [Formula 1] 0.1≦[B / (A+B)]×100(%)≦15
[0161] In the above formula 1, A is the total thickness of the first negative electrode active material layer, which is 30 μm or more and 150 μm or less, B is the total thickness of the second negative electrode active material layer.
[0162] In one embodiment of the present application, the formula 1 may satisfy the range of 0.1≦[B / (A+B)]×100(%)≦15, preferably 0.3≦[B / (A+B)]×100(%)≦14.5, and more preferably 1.5≦[B / (A+B)]×100(%)≦14.5.
[0163] The negative electrode for a lithium secondary battery according to the present application has a double layer structure according to a specific composition, and further has a feature of extremely reducing the probability of problems caused by lithium deposition by controlling the thickness range within the range of the above formula 1. That is, in the negative electrode for a lithium secondary battery according to the present application, since the second negative electrode active material layer is present at the uppermost end, lithium deposition due to the above-mentioned graphite-based active material is formed between the first negative electrode active material layer and the second negative electrode active material layer, so that the formation of lithium dendrites on the surface of the negative electrode can be suppressed, and there is no short circuit problem due to the above-mentioned graphite-based active material, and since the silicon potential is high, lithium smoothly moves to the second negative electrode active material layer.
[0164] In this way, the negative electrode for a lithium secondary battery according to the present application is characterized in that it has a double layer structure in which the first negative electrode active material layer and the second negative electrode active material layer have a specific composition and thickness in order to obtain the advantage of rapid charging of an electrode using a high content of Si particles as a single-layer active material, while resolving the disadvantages of having such an electrode, such as the problems of surface deterioration, uniformity during pre-lithiation, and life characteristics.
[0165] In one embodiment of the present application, the thickness of the first negative electrode active material layer may be 80% or more and 95% or less based on 100% of the total thickness of the first negative electrode active material layer and the second negative electrode active material layer.
[0166] In one embodiment of the present application, the negative electrode for a lithium secondary battery may be a pre-lithiated negative electrode.
[0167] In one embodiment of the present application, a step of preparing a negative electrode current collector layer; a step of applying a first negative electrode active material layer composition to one or both surfaces of the negative electrode current collector layer to form a first negative electrode active material layer; and a step of applying a second negative electrode active material layer composition to the opposite surface of the first negative electrode active material layer in contact with the negative electrode current collector layer to form a second negative electrode active material layer; A method for manufacturing a negative electrode for a lithium secondary battery, wherein the second negative electrode active material includes one or more selected from the group consisting of SiOx (x = 0), SiOx (0 < x < 2), and SiC, and the first negative electrode active material includes one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of alloying with lithium, and a lithium-containing nitride. Based on 100 parts by weight of the first negative electrode active material, the silicon-based active material is included in an amount of 5 parts by weight or less, and a method for manufacturing a negative electrode for a lithium secondary battery satisfying Formula 1 is provided.
[0168] In the method for manufacturing the negative electrode, the composition and content included in each step can apply the foregoing content.
[0169] In one embodiment of the present application, a step of applying a first negative electrode active material layer composition to one or both surfaces of the negative electrode current collector layer to form a first negative electrode active material layer is provided.
[0170] That is, the step is a step of forming an active material layer on the negative electrode current collector layer, and in the double layer structure, it can mean a step of forming an active material layer on the surface (lower layer part) in contact with the current collector layer.
[0171] In one embodiment of the present application, applying the first negative electrode active material layer composition includes a step of applying and drying a first negative electrode slurry including the first negative electrode active material layer composition and a negative electrode slurry solvent.
[0172] At this time, the solid content of the first negative electrode slurry may satisfy the range of 10% to 50%, preferably 2% to 45%.
[0173] In one embodiment of the present application, forming the first negative electrode active material layer may include mixing the first negative electrode slurry; and coating the mixed first negative electrode slurry on one or both sides of the negative electrode current collector layer, and the coating may be performed using a coating method commonly used in the art.
[0174] In one embodiment of the present application, a step of forming a second negative electrode active material by coating a second negative electrode active material layer composition on a surface of the first negative electrode active material layer opposite to a surface in contact with the negative electrode current collector layer is provided.
[0175] That is, the step refers to a step of forming a second negative electrode active material layer on the first negative electrode active material layer, and may refer to a step of forming an active material layer on a surface (upper layer) away from a current collector layer in a double layer structure.
[0176] In one embodiment of the present application, applying the second negative electrode active material layer composition includes applying and drying a second negative electrode slurry including the second negative electrode active material layer composition; and a negative electrode slurry solvent.
[0177] In this case, the solid content of the second negative electrode slurry may be in the range of 10% to 40%.
[0178] In one embodiment of the present application, there is provided a method for manufacturing a negative electrode for a lithium secondary battery, wherein the forming of the second negative electrode active material layer includes: mixing the second negative electrode slurry; and coating the mixed second negative electrode slurry on a surface of the first negative electrode active material layer opposite to a surface in contact with the negative electrode current collector layer.
[0179] The coating may be performed using any coating method commonly used in the art.
[0180] The description of the forming of the first negative electrode active material layer may be similarly applied to the forming of the second negative electrode active material layer.
[0181] In one embodiment of the present application, there is provided a method for manufacturing a negative electrode for a lithium secondary battery, wherein the step of forming the second negative electrode active material layer on the first negative electrode active material layer includes a wet on dry process or a wet on wet process.
[0182] In one embodiment of the present application, the wet-on-dry process may refer to a process of applying a first negative electrode active material layer composition, completely drying the composition, and applying a second negative electrode active material layer composition thereon, and the wet-on-wet process refers to a process of applying a first negative electrode active material layer composition, without drying the composition, and applying a second negative electrode active material layer composition thereon.
[0183] In particular, the wet on dry process involves coating a first negative electrode active material layer composition, completely drying it, and then coating a second negative electrode active material layer composition on top of it, and through this process, the first negative electrode active material layer and the second negative electrode active material layer can have a clear boundary, which allows the compositions contained in the first negative electrode active material layer and the second negative electrode active material layer to be formed as a double layer without being mixed.
[0184] In one embodiment of the present application, the negative electrode slurry solvent may be used without limitation as long as it can dissolve the first negative electrode active material layer composition and the second negative electrode active material layer composition, and specifically, water or NMP may be used.
[0185] In one embodiment of the present application, there is provided a method for manufacturing a negative electrode for a lithium secondary battery, the method including a step of pre-lithiating a negative electrode in which a first negative electrode active material layer and a second negative electrode active material layer are formed on the negative electrode current collector, the step of pre-lithiating the negative electrode including a lithium electrolytic plating process; a lithium metal transfer process; a lithium metal deposition process; or a stabilized lithium metal powder (SLMP) coating process.
[0186] The negative electrode for a lithium secondary battery as described above includes a layer containing a carbon-based active material as a main active material for enhancing the life span and capacity characteristics as a first negative electrode active material layer, and includes a layer containing the above-mentioned silicon-based active material and having a specific thickness as a second negative electrode active material layer, so that it can have the advantage of fast charging. Furthermore, since the first negative electrode active material has the above-mentioned composition and is highly irreversible, it can have a particularly advantageous effect during a pre-lithiation process in which the negative electrode is pre-charged. Compared to the case where only the first negative electrode active material layer or the second negative electrode active material layer is applied, it has the first and second negative electrode active materials having the above-mentioned double layer composition, so that it is possible to maximize the capacity characteristics along with fast charging.
[0187] In one embodiment of the present application, the porosity of the first and second negative electrode active material layers may be in the range of 10% or more and 60% or less.
[0188] In still another embodiment, the porosity of the first and second negative electrode active material layers may be in the range of 10% or more and 60% or less, preferably 20% or more and 50% or less, and more preferably 30% or more and 45% or less.
[0189] The porosity varies depending on the composition and content of the active material, conductive material, and binder contained in the first and second negative electrode active material layers, and is characterized in that the electrical conductivity and resistance of the electrode are in appropriate ranges.
[0190] In one embodiment of the present application, there is provided a lithium secondary battery including: a positive electrode; a negative electrode for a lithium secondary battery according to the present application; a separator disposed between the positive electrode and the negative electrode; and an electrolyte.
[0191] A secondary battery according to an embodiment of the present specification may include the negative electrode for a lithium secondary battery described above. Specifically, the secondary battery may include a negative electrode, a positive electrode, a separator interposed between the positive electrode and the negative electrode, and an electrolyte, and the negative electrode is the same as the negative electrode described above. The negative electrode has been described above, so a detailed description thereof will be omitted.
[0192] The positive electrode may include a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector and including the positive electrode active material.
[0193] In the positive electrode, the positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. can be used. In addition, the positive electrode current collector can usually have a thickness of 3 μm to 500 μm, and fine irregularities can be formed on the surface of the current collector to increase the adhesive force of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0194] The positive electrode active material may be a commonly used positive electrode active material. Specifically, the positive electrode active material may be a layered compound such as lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), or a compound substituted with one or more transition metals; a lithium iron oxide such as LiFe3O4; 1+c1 Mn 2-c1 O4 (0≦c1≦0.33), lithium manganese oxides such as LiMnO3, LiMn2O3, LiMnO2; lithium copper oxide (Li2CuO2); vanadium oxides such as LiV3O8, V2O5, Cu2V2O7; chemical formula LiNi 1-c2 M c2 Lithium nickel oxide with Ni site represented by the chemical formula LiMnO2 (wherein M is at least one selected from the group consisting of Co, Mn, Al, Cu, Fe, Mg, B and Ga, and satisfies 0.01≦c2≦0.3); 2-c3 M c3Examples of the lithium manganese composite oxide include, but are not limited to, lithium manganese composite oxide represented by Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Co, Ni, Fe, Cr, Zn, and Ta, and satisfies 0.01≦c3≦0.1) or Li2Mn3MO8 (wherein M is at least one selected from the group consisting of Fe, Co, Ni, Cu, and Zn); and LiMn2O4 in which part of the Li in the chemical formula is replaced with an alkaline earth metal ion. The positive electrode may be Li metal.
[0195] The positive electrode active material layer may contain a positive electrode conductive material and a positive electrode binder in addition to the above-mentioned positive electrode active material.
[0196] In this case, the positive electrode conductive material is used to impart conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed.Specific examples include graphite such as natural graphite and artificial graphite; carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture.
[0197] The positive electrode binder plays a role in improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the positive electrode current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and one or more of these may be used alone or in combination.
[0198] The separator separates the negative electrode and the positive electrode and provides a passage for lithium ions to move. Any separator that is generally used in secondary batteries can be used without any particular restrictions. In particular, a separator that has low resistance to ion movement of the electrolyte and excellent electrolyte humidification ability is preferred. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, a coated separator containing a ceramic component or a polymeric substance may be used to ensure heat resistance or mechanical strength, and may be selectively used in a single layer or multilayer structure.
[0199] Examples of the electrolyte include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel-type polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the manufacture of lithium secondary batteries, but are not limited to these.
[0200] Specifically, the electrolyte may include a non-aqueous organic solvent and a metal salt.
[0201] Examples of the non-aqueous organic solvent include aprotic organic solvents such as N-methyl-2-pyrrolidinone, propylene carbonate, ethylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, gamma-butyrolactone, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, phosphoric acid triester, trimethoxymethane, dioxolane derivatives, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, propylene carbonate derivatives, tetrahydrofuran derivatives, ethers, methyl propionate, and ethyl propionate.
[0202] In particular, ethylene carbonate and propylene carbonate, which are cyclic carbonates among the carbonate-based organic solvents, are preferably used because they are high-viscosity organic solvents with high dielectric constants and good dissociation of lithium salts. When such cyclic carbonates are mixed with linear carbonates having low viscosity and low dielectric constants, such as dimethyl carbonate and diethyl carbonate, in an appropriate ratio, an electrolyte having high electrical conductivity can be produced, and therefore these can be used more preferably.
[0203] The metal salt may be a lithium salt, which is a substance that is easily dissolved in the non-aqueous electrolyte. For example, the anion of the lithium salt may be F - , Cl - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , PF6 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2- , (CF3)5PF - , (CF3)6P - , CF3SO3 - , CF3CF2SO3 - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2(CF3)2CO - , (CF3SO2)2CH - , (SF5)3C - , (CF3SO2)3C - , CF3(CF2)7SO3 - , CF3CO2 - , CH3CO2 - , SCN - and (CF3CF2SO2)2N - One or more selected from the group consisting of:
[0204] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, and aluminum trichloride for the purposes of improving the life characteristics of the battery, suppressing a decrease in battery capacity, and improving the discharge capacity of the battery.
[0205] One embodiment of the present invention provides a battery module including the secondary battery as a unit cell, and a battery pack including the same. The battery module and the battery pack include the secondary battery having high capacity, high rate-limiting characteristics, and high cycle characteristics, and can be used as a power source for medium- to large-sized devices selected from the group consisting of electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, and power storage systems. EXAMPLES
[0206] Below, preferred examples are presented to aid in understanding the present invention. However, these examples are intended to illustrate the present description, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present description. Naturally, such changes and modifications fall within the scope of the appended claims.
[0207] <Example> <Production of negative electrodes> Example 1: Preparation of negative electrode Preparation of the first negative electrode active material layer A first negative electrode active material layer composition was prepared using SiO (average particle size (D50): 3.5 μm) as a silicon-based active material, artificial graphite, a first conductive material, a third conductive material, and CMC:SBR as a binder in a weight ratio of 4.779:90.794:0.982:0.018:1.127:2.3. The first negative electrode slurry was prepared by adding the composition to distilled water as a solvent for forming a negative electrode slurry (solid concentration 45 wt%).
[0208] The first conductive material is carbon black C (specific surface area: 58 m 2 / g, diameter: 37 nm), and the third conductive material is a carbon nanotube.
[0209] The mixing method was as follows: the first conductive material, the third conductive material, the binder and the water were dispersed using a homomixer at 2500 rpm for 30 minutes, the active material was then added, and the mixture was dispersed at 2500 rpm for 30 minutes to prepare a slurry.
[0210] The first negative electrode slurry was applied at 9.312 mg / cm to both sides of a copper current collector (thickness: 8 μm) as a negative electrode current collector. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a first negative electrode active material layer (thickness: 114 μm).
[0211] Preparation of second negative electrode active material layer A second negative electrode active material layer composition was prepared by mixing SiO (average particle size (D50): 5 μm) as a silicon-based active material, a second conductive material, a third conductive material, and polyacrylamide as a binder in a weight ratio of 80:9.6:0.4:10. The second negative electrode active material layer composition was prepared by adding the mixture to distilled water as a solvent for forming a negative electrode slurry (solid concentration 25 wt%).
[0212] The second conductive material is plate-shaped graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the third conductive material is carbon nanotubes.
[0213] The mixing method was as follows: the second conductive material, the third conductive material, the binder and the water were dispersed using a homomixer at 2500 rpm for 30 minutes, the active material was then added, and the mixture was dispersed at 2500 rpm for 30 minutes to prepare a slurry.
[0214] The second negative electrode slurry was applied to the first negative electrode active material layer at a concentration of 0.464 mg / cm 2 The coating was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a second negative electrode active material layer (thickness: 5.6 μm). In this case, Equation 1 satisfied the range of 4.59.
[0215] A negative electrode was manufactured in the same manner as in Example 1, except that the thickness and the range of Formula 1 in the following Table 1 were satisfied. For reference, in the evaluated Examples and Comparative Examples, a first negative electrode active material layer and a second negative electrode active material layer were formed on both sides of a negative electrode current collector layer, and the thicknesses (loading amounts) of the first negative electrode active material layer and the second negative electrode active material layer refer to the thicknesses of the entire first negative electrode active material layer and the second negative electrode active material layer formed on both sides.
[0216] [Table 1]
[0217] Comparative Example 4: Production of negative electrode In preparing the first negative electrode active material layer of Example 1, a silicon-based active material, SiO (average particle size (D50): 3.5 μm), artificial graphite, a first conductive material, a third conductive material, and a binder, CMC:SBR, were used in a weight ratio of 7:88.573:0.982:0.018:1.127:2.3 instead of 4.779:90.794:0.982:0.018:1.127:2.3, to prepare a negative electrode in the same manner as in Example 1.
[0218] Comparative Example 5: Production of negative electrode Preparation of the first negative electrode active material layer A first negative electrode active material layer composition was prepared by mixing artificial graphite, a first conductive material, a third conductive material, and CMC:SBR as a binder in a weight ratio of 95.5:0.98:0.02:1:2.5. The first negative electrode slurry was prepared by adding the mixture to distilled water as a solvent for forming a negative electrode slurry (solid concentration 45% by weight).
[0219] The first conductive material is carbon black C (specific surface area: 58 m 2 / g, diameter: 37 nm), and the third conductive material is a carbon nanotube.
[0220] The mixing method was as follows: the first conductive material, the third conductive material, the binder and the water were dispersed using a homomixer at 2500 rpm for 30 minutes, the active material was then added, and the mixture was dispersed at 2500 rpm for 30 minutes to prepare a slurry.
[0221] The first negative electrode slurry was applied at 8.012 mg / cm on both sides of a copper current collector (thickness: 8 μm) as a negative electrode current collector. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a first negative electrode active material layer (thickness: 98.2 μm).
[0222] Preparation of second negative electrode active material layer A second negative electrode active material layer composition was prepared by mixing SiO (average particle size (D50): 5 μm) as a silicon-based active material, a second conductive material, a third conductive material, and polyacrylamide as a binder in a weight ratio of 80:9.6:0.4:10. The second negative electrode active material layer composition was prepared by adding the mixture to distilled water as a solvent for forming a negative electrode slurry (solid concentration 25 wt%).
[0223] The second conductive material is plate-shaped graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the third conductive material is carbon nanotubes.
[0224] The mixing method was as follows: the second conductive material, the third conductive material, the binder and the water were dispersed using a homomixer at 2500 rpm for 30 minutes, the active material was then added, and the mixture was dispersed at 2500 rpm for 30 minutes to prepare a slurry.
[0225] The second negative electrode slurry was applied to the first negative electrode active material layer at a concentration of 0.908 mg / cm 2 The coating was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a second negative electrode active material layer (thickness: 11.2 μm). In this case, Equation 1 satisfied the range of 10.54.
[0226] Comparative Examples 5 to 8 In Comparative Example 5, a negative electrode was manufactured in the same manner as in Comparative Example 5, except that the thickness and the range of Formula 1 in the following Table 2 were satisfied. For reference, in the evaluated Examples and Comparative Examples, a first negative electrode active material layer and a second negative electrode active material layer were formed on both sides of a negative electrode current collector layer, and the thicknesses (loading amounts) of the first negative electrode active material layer and the second negative electrode active material layer refer to the thicknesses of the entire first negative electrode active material layer and the second negative electrode active material layer formed on both sides.
[0227] [Table 2]
[0228] Comparative Example 9: Production of negative electrode An active material layer composition was prepared by mixing silicon-based active material Si (average particle size (D50): 5 μm), a first conductive material, and polyacrylamide as a binder in a weight ratio of 70:20:10. A negative electrode slurry was prepared by adding the mixture to distilled water as a solvent for forming a negative electrode slurry (solid concentration 25 wt%).
[0229] The first conductive material is carbon black C (specific surface area: 58 m 2 / g, diameter: 37 nm) is used.
[0230] As for the mixing method, the first conductive material, binder and water were dispersed using a homomixer at 2500 rpm for 30 minutes, and then the active material was added, followed by dispersion at 2500 rpm for 30 minutes to prepare a slurry.
[0231] The negative electrode current collector was a copper current collector (thickness: 8 μm) on both sides of which the negative electrode slurry was applied at 85 mg / 25 cm. 2 The coated layer was roll pressed and dried in a vacuum oven at 130° C. for 10 hours to form a negative electrode active material layer (thickness: 25.78 μm).
[0232] Comparative Example 10: Production of negative electrode A negative electrode was manufactured in the same manner as in Comparative Example 9, except that the active material layer composition was prepared using Si (average particle size (D50): 5 μm), SiO (average particle size (D50): 3.5 μm), a first conductive material, and polyacrylamide as a binder in a weight ratio of 52.5:17.5:20:10.
[0233] The first conductive material is carbon black C (specific surface area: 58 m 2 / g, diameter: 37 nm), and the second conductive material is plate-shaped graphite (specific surface area: 17 m 2 / g, average particle size (D50): 3.5 μm), and the third conductive material is carbon nanotubes.
[0234] Comparative Example 11: Production of negative electrode A negative electrode was fabricated in the same manner as in Example 1, except that the second negative electrode active material layer composition was prepared as follows: the second negative electrode slurry contained artificial graphite, the first conductive material, the third conductive material, and CMC:SBR as a binder in a weight ratio of 95.5:0.98:0.02:1:2.5, and the first negative electrode slurry contained SiO (average particle size (D50): 5 μm) as a silicon-based active material, the second conductive material, the third conductive material, and polyacrylamide as a binder in a weight ratio of 80:9.6:0.4:10.
[0235] <Secondary battery manufacturing> LiNi as the positive electrode active material 0.6 Co 0.2 Mn 0.2 O2 (average particle size (D50): 15 μm), carbon black (product name: Super C65, manufacturer: Timcal) as a conductive material, and polyvinylidene fluoride (PVdF) as a binder were added in a weight ratio of 97.21:1.2:1.59 to N-methyl-2-pyrrolidone (NMP) as a solvent for forming a positive electrode slurry to prepare a positive electrode slurry (solid concentration 78 wt%).
[0236] The positive electrode current collector was an aluminum current collector (thickness: 12 μm) and the positive electrode slurry was applied to both sides of the aluminum current collector at a rate of 439.1 mg / 25 cm. 2 The coated layer was rolled and dried in a vacuum oven at 130° C. for 10 hours to form a positive electrode active material layer (thickness: 105.5 μm) to prepare a positive electrode (thickness of positive electrode: 117.5 μm, porosity: 26%).
[0237] A polyethylene separator was interposed between the positive electrode and the negative electrode of Example 1, and an electrolyte was injected therebetween to prepare the secondary battery of Example 1.
[0238] The electrolyte was an organic solvent in which fluoroethylene carbonate (FEC) and diethyl carbonate (DEC) were mixed in a volume ratio of 30:70, to which vinylene carbonate was added at 3 wt% based on the total weight of the electrolyte, and LiPF6 was added as a lithium salt at a concentration of 1M.
[0239] Except for using the negative electrodes of the above-mentioned Examples and Comparative Examples, secondary batteries were fabricated in the same manner as described above.
[0240] Experimental example 1: Monocell life evaluation The secondary battery manufactured as described above was subjected to a life evaluation using an electrochemical charger / discharger, and the capacity retention rate was evaluated. The secondary battery was subjected to 200 cycles of charging (0.33C CC / CV charging, 4.2V, 0.05C cut) and discharging (0.33C CC discharging, 2.5V cut), and the capacity retention rate was confirmed.
[0241] The capacity retention rate at the 200th charge was evaluated according to the following formula, and the results are shown in Table 3 below. Capacity retention rate (%) = {(discharge capacity at 200th cycle) / (discharge capacity at 1st cycle)} x 100
[0242] [Table 3]
[0243] As can be seen from Table 3, Examples 1 to 3 of the present invention were found to have superior life performance compared to Comparative Examples 1 to 4 and 8 to 11. It was found that when a silicon-based material that is affected by volume expansion and contraction due to charging and discharging is used, the life performance is partially inferior, and the life performance is consistently superior as the specific gravity of a graphite-based material that does not expand or contract in volume is higher.
[0244] In Comparative Examples 2 and 3, the compositions of the first and second negative electrode active material layers are the same as in Example 1, but the thickness range of the first negative electrode active material layer is not satisfied. In the case of Comparative Example 3, the thickness of the first negative electrode active material layer is increased and capacity characteristics are ensured, but the content of the silicon-based active material in the first negative electrode active material layer is increased, and it was confirmed that the life performance is inferior, similar to Comparative Example 4.
[0245] It was confirmed that in Comparative Examples 1 and 8, the ratio of silicon-based material contained in the upper layer was too high, resulting in poor life performance. It was confirmed that in Comparative Examples 9 and 10, where the active material capacity was even larger, the life performance was even worse. This is because the silicon-based active material, which has a capacity 10 times that of graphite, was evaluated in the same voltage range as graphite, resulting in a large degree of expansion and contraction.
[0246] In Comparative Example 11, the upper and lower layers were inverted, and the lower layer in contact with the foil expanded and contracted in volume, causing electrode detachment, resulting in a decrease in performance.
[0247] For reference, Comparative Examples 5 to 7 did not contain a silicon-based active material in the first negative electrode active material layer, and showed life performance similar to that of the Examples. However, in the rapid charging evaluation described below, it was confirmed that the performance was very poor because the silicon-based active material was not contained.
[0248] Experimental example 2: Rapid charging evaluation The secondary battery manufactured above was subjected to a rapid charge evaluation using an electrochemical charger and the charging time was confirmed. The rapid charge evaluation was carried out by performing 3 cycles of 0.33C / 0.33C, and the last third discharge capacity was determined as the cell capacity. Then, in the fourth cycle, the battery was first charged at 0.33C, and then 80% of the third discharge capacity was discharged, that is, the battery was discharged at 0.33C until the voltage at which 20% of the cell capacity remained, and then charged to 80% at 4.5C. In conclusion, an evaluation was carried out to confirm the time it took to charge the cell to 20-80% capacity, and the results are shown in Table 4.
[0249] [Table 4]
[0250] Silicon-based active materials have a larger capacity than graphite-based active materials, so even if the same C-rate current is applied, a higher C-rate is applied to graphite-based active materials. In comparison, silicon-based active materials are applied with a lower C-rate, forming a lower resistance, which lengthens the CC section during charging and shortens the charging time. Conversely, if the resistance is high, it will reach 4.2V sooner, CV will be applied, and the current will be lower, resulting in a longer charging time.
[0251] In Table 4, Examples 1 to 3, which contain a specific amount of silicon-based active material in the lower layer, have a relatively short charging time. Comparative Examples 5 to 7, which contain only graphite-based active material in the lower layer, have excellent life performance, but are significantly inferior in rapid charging performance to Examples 1 to 3.
[0252] In Comparative Examples 1 and 8, the proportion of the upper layer using silicon was increased, and it was confirmed that the charging performance was improved. However, as can be seen from Table 3, it was confirmed that the results showed that the life performance was very poor. In Comparative Examples 9 and 10, pure Si with a large capacity of the active material was used, which is suitable for rapid charging, but the life performance was also very poor. Furthermore, in Comparative Example 11, a graphite layer was formed in the upper layer, and it was confirmed that it was very poor for rapid charging. [Explanation of symbols]
[0253] 10...Second negative electrode active material layer 20...first negative electrode active material layer 30 Negative electrode current collector layer
Claims
1. Negative electrode current collector layer; a first negative electrode active material layer provided on one or both sides of the negative electrode current collector layer; and a second negative electrode active material layer provided on a surface of the first negative electrode active material layer opposite to a surface in contact with the negative electrode current collector layer; A negative electrode for a lithium secondary battery comprising: the first negative electrode active material layer includes a first negative electrode active material layer composition including a first negative electrode active material, and the second negative electrode active material layer includes a second negative electrode active material layer composition including a second negative electrode active material, the second negative electrode active material layer includes one or more selected from the group consisting of SiOx (x=0), SiOx (0<x<2), and SiC; The first negative electrode active material includes at least one selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride, The silicon-based active material is included in an amount of 5 parts by weight or less based on 100 parts by weight of the first negative electrode active material, A negative electrode for a lithium secondary battery that satisfies the following formula 1: [Formula 1] 0.1≦[B / (A+B)]x100(%)≦15 In the above formula 1, A is the total thickness of the first negative electrode active material layer, which is 30 μm or more and 150 μm or less, B is the total thickness of the second negative electrode active material layer.
2. 2. The negative electrode of claim 1, wherein the first negative electrode active material comprises a mixture of one or more selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride, and the silicon-based active material is present in an amount of 1 part by weight to 5 parts by weight based on 100 parts by weight of the first negative electrode active material.
3. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the silicon-based active material comprises at least one selected from the group consisting of SiOx (0<x<2), SiC, and a Si alloy.
4. 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the silicon-based active material comprises SiOx (0<x<2); or SiC.
5. The negative electrode of claim 1 , wherein the second negative electrode active material is 60 parts by weight or more based on 100 parts by weight of the second negative electrode active material layer composition.
6. 2 . The negative electrode for a lithium secondary battery according to claim 1 , wherein the second negative electrode active material layer has a total thickness of 1 μm or more and 20 μm or less.
7. The loading amount of the first negative electrode active material layer composition is 5 mg / cm 2 20mg / cm or more 2 is as follows: The loading amount of the second negative electrode active material layer composition is 0.1 mg / cm 2 5mg / cm or more 2 2. The negative electrode for a lithium secondary battery according to claim 1, wherein:
8. the first negative electrode active material layer composition further includes at least one selected from the group consisting of a first negative electrode conductive material; and a first negative electrode binder; 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the second negative electrode active material layer composition further comprises at least one selected from the group consisting of a second negative electrode conductive material; and a second negative electrode binder.
9. The carbon-based active material includes graphite, The graphite includes artificial graphite and natural graphite; 2. The negative electrode for a lithium secondary battery according to claim 1, wherein the weight ratio of the artificial graphite to the natural graphite is 5:5 to 9.5:0.
5.
10. Providing a negative electrode current collector layer; applying a first negative electrode active material layer composition to one or both surfaces of the negative electrode current collector layer to form a first negative electrode active material layer; and forming a second negative electrode active material layer by applying a second negative electrode active material composition to a surface of the first negative electrode active material layer opposite to a surface in contact with the negative electrode current collector layer; A method for producing a negative electrode for a lithium secondary battery, comprising: the second negative electrode active material includes at least one selected from the group consisting of SiOx (x=0), SiOx (0<x<2), and SiC; The first negative electrode active material includes at least one selected from the group consisting of a carbon-based active material, a silicon-based active material, a metal-based active material capable of forming an alloy with lithium, and a lithium-containing nitride, The silicon-based active material is included in an amount of 5 parts by weight or less based on 100 parts by weight of the first negative electrode active material, A method for producing a negative electrode for a lithium secondary battery, which satisfies formula 1: [Formula 1] 0.1≦[B / (A+B)]x100(%)≦15 In the above formula 1, A is the total thickness of the first negative electrode active material layer, which is 30 μm or more and 150 μm or less, B is the total thickness of the second negative electrode active material layer.
11. pre-lithiating the negative electrode having the first negative electrode active material layer and the second negative electrode active material layer formed on the negative electrode current collector layer; 11. The method of claim 10, wherein the prelithiation of the negative electrode comprises a lithium electrolytic plating process; a lithium metal transfer process; a lithium metal deposition process; or a stabilized lithium metal powder (SLMP) coating process.
12. positive electrode; The negative electrode for a lithium secondary battery according to any one of claims 1 to 9; A separator disposed between the positive electrode and the negative electrode; and electrolyte; A lithium secondary battery comprising:
Citation Information
Patent Citations
Negative electrode for nonaqueous secondary battery, its manufacturing method, and nonaqueous secondary battery
JP2007179864A
Rainwater controlling apparatus for easying upkeeping a furnished with perpendicularity filtering floor
KR101995494B1
Anode for lithium ion battery
JP2009080971A
KR20210039599A